Scholars in Action (2 vols) The Practice of Knowledge and the Figure of the Savant in the 18th Century - Holenstein, André; Steinke, Hubert; Stuber, Martin (History of Science and Medicine Library, 2013)
In Scholars in Action, an international group of 40 authors open up new perspectives on the eighteenth-century culture of knowledge, with a particular focus on scholars and their various practices.; Readership: All interested in the Republic of Letters, the history of Enlightenment and the history of early modern knowledge, scholarship and science.